(untitled) (Experimental biology, 2023)
This article discusses the issues of low-temperature preservation of sperm of sturgeon fish. The aim of the work is to study the effect of the freezing rate on the sperm quality indicators of sturgeon fish and the dependence of these indicators among themselves. The material for the research was the sperm of harvested males of sterlet and stellate sturgeon at the Ural-Atyrau sturgeon fish hatchery. When studying the effect of the freezing rate on the quality of sperm of sturgeon fish, optimal speeds were determined at the stages of stepwise freezing. When freezing sterlet sperm, the highest result was obtained at an optimal freezing rate of 170C/min with sperm motility of 76.8±1.25% and sperm lifetime of 216.2±1.44sec. The sperm of the male stellate sturgeon frozen in straws had a high rate at the beginning of freezing in the range of 15-480С/min, which affected the quality of the sperm of the stellate sturgeon, whose sperm motility ranged from 12.0-19.5%, the life time of the sperm was 228.5-373.75seconds. Relatively good results were obtained from the sperm of male stellate sturgeon frozen in Epindorf tubes, which had the highest freezing rate up to 200C/min. The motility of the sperms ranged from 27.75-44.75%, the lifetime of the sperms 393.25-674.5seconds. When studying, there is a direct relationship between the mobility and the lifetime of sperm of sturgeon fish, and also from the obtained research results it can be seen that the most optimal freezing rate of sperm of these species of sturgeon fish is a speed of up to 200C /min, the capacity in which it is advisable to freeze samples are Epindorf tubes, 0.5ml in volume, and the multi-stage freezing mode using special boxing.